Novel graphene UHMWPE nanocomposites prepared by polymerization filling using single-site catalysts supported on functionalized graphene nanosheet dispersions - Stürzel, Markus Roland; Enders, Markus (Macromolecules, 2012)
Novel families of ultrahigh-molecular-weight polyethylene (UHMWPE) nanocomposites, containing uniformly dispersed, functionalized graphene (FG) nanosheets, were prepared by means of the polymerization filling technique (PFT). Unparalleled by any other carbon and boehmite nanocomposites, FG/UHMWPE exhibited an unusual simultaneous improvement in stiffness, elongation at break, and effective nucleation of polyethylene crystallization at only 1 wt % FG content. FG nanosheets are ultrathin—with a thickness of only one carbon atom and lateral dimensions of several micrometers. Owing to the presence of surface hydroxyl groups on the FG, single FG/methylaluminoxane (MAO) nanosheets can be effectively dispersed in n-heptane, thus enabling immobilization of an MAO-activated chromium (Cr1) single-site catalyst on FG. In contrast to nanometer-scale carbon black (CB), multiwall carbon nanotubes (CNT), graphite, and nanoboehmite, which failed to form stable dispersions, FG/MAO/Cr1 afforded the highest catalyst activities and excellent morphological control. In polymerization filling, the integration of a nanoparticle dispersion into the polymerization process eliminated the need for special safety and handling precautions typically required by conventional compounding of nanoparticles with ultralow bulk densities.
Gesehen am 11.06.2018